Rhabdosoma brevicaudatum Stebbing 1888 - Gasca, Rebeca; Hendrickx, Michel E. (Zenodo, 2022)
Rhabdosoma brevicaudatum Stebbing, 1888 Rhabdosoma brevicaudatum Stebbing, 1888: 350 (key), 357; Brusca, 1981: 12 (list), 32 (key), fig. 21d; Siegel-Causey, 1982: 357; Vinogradov et al ., 1996: 536 (key), 540‒541, fig. 233; García Madrigal, 2007: 157 (list); Gasca, 2009: 89 (tab. 1); Lavaniegos & Hereu, 2009: 152 (appendix); Lavaniegos, 2014: 5 (tab. 1); Valencia et al ., 2013: 52 (tab. 1); Zeidler, 2016: 79 (passim), fig. 36D, 80 (key); Violante-Huerta et al ., 2021: 81 (tab. 1), 84‒85, fig. 2C. Material examined . 4F in one locality (Fig. 3). TALUD V. St. 5 (22°00’57”N, 106°40’00”W), December 13, 2000, 4F, MN from surface to ca. 1400 m (TD> 1600 m) (ICML-EMU-12964). Distribution . Subtropical Pacific Ocean, Atlantic Ocean from equator to 40°N; Mediterranean Sea. In the eastern Pacific from California to Costa Rica and Panama (García Madrigal 2007, Valencia et al . 2013, Violante-Huerta et al . 2021, this study). Remarks . The specimens identified as R. brevicaudatum have a very small article on top of callynophore, smaller than in Zeidler’s (2016) key, the telson length is about 1/3 of the length of the double urosomite and does not reach the tip of uropod 2. The specimens examined are very similar to those of R. minor examined herein. Males of this species are not kown. Reported as rare in the central and southern Gulf of California by Siegel-Causey (1982), a pattern confirmed during our study (Fig. 3). Also present in the Mexican portion of the California Current (Lavaniegos & Hereu 2009, Lavaniegos 2014). : Published as part of Gasca, Rebeca & Hendrickx, Michel E., 2022, Pelagic amphipods (Crustacea: Amphipoda: Hyperiidea) in western Mexico. 7 Superfamily Platysceloidea. Family Oxycephalidae, pp. 219-236 in Zootaxa 5105 (2) on page 226, DOI: 10.11646/zootaxa.5105.2.3, http://zenodo.org/record/6332529 : {"references": ["Stebbing, T. R. R. (1888) Report on the Amphipoda collected by H. M. S. Challenger during the years 1873 - 1876. Report on the Scientific Results of the Voyage of H. M. S. Challenger during the years 1873 - 76, Zoology, 29 (Part 67), i - xxiv + 1 - 1737, pls. 1 - 212.", "Brusca, G. J. (1981) Annotated keys to the Hyperiidea (Crustacea: Amphipoda) of North American coastal waters. Allan Hancock Foundation Technical Reports, 5, 1 - 76. https: // doi. org / 10.2307 / 1547968", "Siegel-Causey, D. (1982) Factors determining the distribution of hyperiid Amphipoda in the Gulf of California. Ph. D. Thesis, University of Arizona, Tucson, Arizona, 535 pp.", "Vinogradov, M. E., Volkov, A. F. & Semenova, T. N. (1996) Hyperiid amphipods (Amphipoda, Hyperiidea) of the world oceans. Oxonian Press Pvt. Ltd., New Delhi, 632 pp.", "Lavaniegos, B. E. & Hereu, C. (2009) Seasonal variation in hyperiid amphipod abundance and diversity and influence of mesoscale structures off Baja California. Marine Ecology Progress Series, 394, 137 - 152. https: // doi. org / 10.3354 / meps 08285", "Lavaniegos, B. E. (2014) Pelagic amphipod assemblage associated with subarctic water off the West Coast of the Baja California Peninsula. Journal of Marine Systems, 132, 1 - 12. https: // doi. org / 10.1016 / j. jmarsys. 2013.12.012", "Valencia, B., Lavaniegos, B., Giraldo, A. & Rodriguez-Rubio, E. (2013) Temporal and spatial variation of hyperiid amphipod assemblages in response to hydrographic processes in the Panama Bight, eastern tropical Pacific. Deep-Sea Reseach I, 73, 46 - 61. https: // doi. org / 10.1016 / j. dsr. 2012.11.009", "Zeidler, W. (2016) A review of the families and genera of the superfamily Platysceloidea Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. Zootaxa, 4192 (1), 1 - 136. https: // doi. org / 10.11646 / zootaxa. 4192.1.1", "Violante-Huerta, M., Morales-Ramirez, A. & Sanvicente-Anorve, L. (2021) Anfipodos pelagicos (Amphilochidea, Hyperiidea y Senticaudata) del Pacifico de Costa Rica: nuevos registros y una lista de especies actualizada. Revista de Ciencias Marinas y Costeras, 13 (1), 77 - 97. https: // doi. org / 10.15359 / revmar. 13 - 1.5"]}